2019
DOI: 10.20944/preprints201905.0272.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Habitat Climate Change Vulnerability Index Applied to Major Vegetation Types of the Western Interior United States

Abstract: We applied a framework to assess climate change vulnerability of 52 major vegetation types in the western United States to provide spatially-explicit input to adaptive management decisions. The framework addressed climate exposure and ecosystem resilience; the latter derived from analyses of ecosystem sensitivity and adaptive capacity. Measures of climate change exposure used observed climate change (1981-2014) and then climate projections for the mid-21st century (2040-2069 RCP 4.5). Measures of resilience in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our analysis is based on the NatureServe Terrestrial Ecological Systems, a classification of 642 vegetation ‘types’ that have been extensively described and mapped at high resolution by resource managers in the conterminous US through a combination of remote sensing and extensive ground surveys (Comer et al, ; Gergely & McKerrow, ; Rollins, ) and widely used in ecological assessments (e.g., Aycrigg et al, ; Comer et al, , ; Thorne et al, ). Each of these vegetation types represents a recurring natural plant community defined by dominant and diagnostic plant species and their characteristic environment (Comer et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis is based on the NatureServe Terrestrial Ecological Systems, a classification of 642 vegetation ‘types’ that have been extensively described and mapped at high resolution by resource managers in the conterminous US through a combination of remote sensing and extensive ground surveys (Comer et al, ; Gergely & McKerrow, ; Rollins, ) and widely used in ecological assessments (e.g., Aycrigg et al, ; Comer et al, , ; Thorne et al, ). Each of these vegetation types represents a recurring natural plant community defined by dominant and diagnostic plant species and their characteristic environment (Comer et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Alexander et al [ 12 ] assessed the vulnerability of tropical ecosystems in southern Ecuador and found differences in ecosystem vulnerability under different climate scenarios. Patrick et al [ 13 ] investigated the vulnerability of 52 major vegetation types in the western United States exposed to changes in temperature and precipitation under RCP 4.5 scenarios (RCP4.5, Representative Concentration Pathway 4.5, a moderate emission scenario proposed by the Coupled Model Intercomparison Project Phase 5). Their results showed that by the middle of the 21st century, 33 vegetation types will be faced with high or very high vulnerability, of which more than 50% will have higher regional vulnerability levels.…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach, Comer et al, (2019) created an index to assess habitat vulnerability to climate change by modeling resilience from the inclusion of factors such as intact landscapes, invasive species, alteration of the fire regime, forest insects and risk of diseases. In a recent review, Chambers, Allen e Cushman, (2019) tried to operationalize the concept of resilience from a explicitly spatial conceptual framework.…”
Section: Modeling Terrestrial Biomes Resilience In Brazilmentioning
confidence: 99%